The first case of septicemia due to nontoxigenic Corynebacterium diphtheriae in Poland: case report - Podlasin Regina; Zaleska Maria; Zasada Aleksandra; Seferyńska Ilona (BMC, 2005)
Abstract Background Toxigenic strains of Corynebacterium diphtheriae are well known agent of diphtheria. Nontoxigenic strains can cause atypical course of the disease. Invasive diseases caused by C. diphtheriae occur very rare. Case presentation We have described the first case of septicemia and endocarditis due to nontoxigenic C. diphtheriae biotype gravis in Poland. The patient has not belonged to any group of risk such infection. Conclusion The case presented in this article shows unusual case of infection connected with nontoxigenic C. diphtheriae that took place in the area where have been no cases of diphtheria and other C. diphtheriae infections for near ten years. It shows the importance of identifying Corynebacterium isolates at the species level especially when the strain has been isolated from normally sterile sites.